1990
DOI: 10.1063/1.103246
|View full text |Cite
|
Sign up to set email alerts
|

Surface preparation for the heteroepitactic growth of ceramic thin films

Abstract: The morphology, composition, and crystallographic orientation of the substrate influence the nucleation and growth of deposited thin films. A method for the preparation of controlled, characteristic surfaces is reported. The surfaces are suitable for the heteroepitactic growth of thin films. When used in the formation of electron-transparent thin foils, the substrates can be used to investigate the very early stages of film growth using transmission electron microscopy. The substrate preparation involves the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…In the process of epitaxial high-T c superconducting thin film fabrication by DC sputtering, there are many parameters involved which all have to be taken into account. The YBCO thin film growth conditions of major importance are substrate preparation [5,6], target condition, target-substrate distance, gas mixture, growth temperature, deposition rate, oxygenation temperature and cooling rate. All these parameters should be optimized to obtain reproducible, homogeneous and epitaxial c-axis thin films on different substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of epitaxial high-T c superconducting thin film fabrication by DC sputtering, there are many parameters involved which all have to be taken into account. The YBCO thin film growth conditions of major importance are substrate preparation [5,6], target condition, target-substrate distance, gas mixture, growth temperature, deposition rate, oxygenation temperature and cooling rate. All these parameters should be optimized to obtain reproducible, homogeneous and epitaxial c-axis thin films on different substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In either case, it was necessary to eliminate the damaged surface before coating in order to obtain a clear pattern. This process has been demonstrated directly by TEM (Norton, 1990;Susnitzky and Carter, 1992).…”
Section: Surface Qualitymentioning
confidence: 91%
“…These discs were sintered at 1600 • C for 15 h. All the process was carried out in air. The substrates used in the present study were single side polished (100) MgO single crystal substrates of the dimension 10 mm × 10 mm × 0.5 mm annealed at 1000 • C for 10 h as it is reported that the annealed MgO substrates yield better results [16,17]. The MgO substrate was mounted on a rotating metal disc substrate holder using silver paste, and the metal substrate holder was irradiated by a lamp heater.…”
Section: Methodsmentioning
confidence: 99%